Handbook of cosmeceutical excipients and their safeties - Kwan, Yu Heng (Kidlington, UK : Woodhead Publishing, 2014)
Cosmeceuticals are the latest additions to the health industry and have an ever-expanding market. They are considered to be a marriage between cosmetics and drugs and are defined as preparations applied on the body that may modify the physiological functions of the skin. However, as more cosmeceuticals are being launched in the market and more types of drugs are incorporated into the formulation, the composition of cosmeceuticals is becoming more complex. Handbook of Cosmeceutical Excipients and their Safeties summarises the current evidence relating to cosmeceuticals' side effects and highlig.
3 Skin permeation of cosmetics3.1 Introduction; 3.2 Human skin, barrier properties and challenges to absorption; 3.3 The concept of flux; 3.4 Mathematical modelling of flux; 3.5 In vitro skin permeation testing; 3.6 Skin models for permeation testing; 3.7 Conclusion; 4 Systemic effect ofcosmeceutics -- cancer; 4.1 Introduction; 4.2 Methodology; 4.3 Results; 4.4 Discussion; 4.5 Conclusion; 5 Local effect of cosmeceutics -allergic contact dermatitis; 5.1 Introduction; 5.2 Methodology; 5.3 Results; 5.4 Discussion; 5.5 Conclusion; 5.6 Note (to 'type of assays' on page 64); 6 Essential monographs.
Includes bibliographical references and index.
Print version record.
Keywords: Dermatologic agents; MEDICAL -- Pharmacology; Dermatologic agents; Electronic books